The role of interleukin-33 in chronic rhinosinusitis. Issue 7 (24th November 2016) - Kim, Dong-Kyu; Jin, Hong Ryul; Eun, Kyoung Mi; Mo, Ji-Hun; Cho, Seong H; Oh, Sohee; Cho, David; Kim, Dae Woo
Abstract : Rationale: Interleukin (IL)-33, a new member of the IL-1 family, is constitutively expressed in epithelial tissues and lymphoid organs and plays an important role in the pathogenesis of allergic disease. However, the role of IL-33 in chronic rhinosinusitis with nasal polyps (CRSwNP) remains unclear. Objective: To investigate the role of IL-33 in the pathophysiology of CRSwNP. Methods: We investigated IL-33 expression and its cellular origins in the nasal polyps (NPs) of human subjects by immunohistochemistry (IHC), quantitative reverse transcription PCR (qRT-PCR), and multiplex cytokine assays. Correlations between IL-33 expression and other inflammatory markers were also explored. To investigate the role of IL-33 in CRSwNP, anti-IL-33 antibody was used in a murine model of CRS. Results: Uncinate process tissues from control (19), CRSsNP (61), CRSwNP (69) and NP tissues (71) were used in this study. Increased expression of IL-33 mRNA and protein in patients with CRSwNP compared with controls was observed. The concentration of IL-33 protein in CRSwNP was positively correlated with the number of neutrophils and the expression of several Th1 and Th17 inflammatory markers, including interferon (IFN)-γ, IL-1β, tumour necrosis factor (TNF)-α, IL-17A, IL-22, and various markers for neutrophil recruitment. However, protein levels of IL-5 and quantity of eosinophils were inversely correlated with levels of IL-33. The expression of tissue inhibitor of metalloproteinase (TIMP)-1 was negatively correlated with IL-33 protein levels, while the expression of matrix metalloproteinase (MMP)-2 and MMP-9 was positively correlated with IL-33 protein levels. In animal studies, IL-33 expression was upregulated in the CRSwNP group compared with controls. Anti-IL-33 treatment reduced the thickness of oedematous mucosa, subepithelial collagen deposition, and infiltration of neutrophils, but infiltration of eosinophils was not reduced. This treatment also inhibited the expression of neutrophilic inflammatory cytokines, but not IL-4. In addition, the expression of intracellular adhesion molecule 1, vascular adhesion molecule 1 and CXCL-2 in the nasal mucosa was suppressed in mice treated with anti-IL-33 antibody. Conclusions: Our data suggest a role for IL-33 in the pathogenesis of CRSwNP via neutrophil recruitment. Therefore, anti-IL-33 may provide a new treatment strategy to target infiltrating neutrophils in CRSwNP.